Pharmacologic Prevention of Migraine: A Narrative Review of the State of the Art in 2018. (23rd August 2018) - Loder, Elizabeth; Rizzoli, Paul
Abstract : This paper describes current non‐antibody pharmacologic approaches to the prevention of migraine in adults. Preventive therapy should be considered for patients with migraine who routinely have more than 6 headache days per month or in other special circumstances. Choices for preventive therapy are based on patient preferences about side effects and evidence of efficacy. The evidence level and commonly used doses for selected categories of migraine preventive medication are reviewed, including antiepileptic drugs, antihypertensive drugs, and antidepressants. Propranolol, timolol, topiramate, and divalproex sodium are approved for migraine prevention by the US FDA. OnabotulinumtoxinA is approved for prevention of chronic migraine. Several off‐label drugs, especially lisinopril, candesartan, and amitriptyline also have good evidence of benefit. The spectrum of response to preventive therapy varies; in general, complete cessation of headaches is uncommon, although there are "super‐responders" to every therapy, as illustrated by patient reports of dramatic responses to treatment. Preventive treatment should be started at a low dose and doses increased slowly until therapeutic benefit is achieved or side effects preclude continued use.